Improved Understanding of Student's Learning Concept and Motivation in Inclined Plane Material by PhET Simulation - Rohim, Ahmad Minanur; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2020)
This research is aimed to improve the understanding of the concept and the motivation of learning physics students on inclined plane material class of Eighth grade of MTs NU I'anatuth-Thullab Mutih Kulon Demak School Year of 2020/2021. This study conducted at the eighth grade of students as the subject consisting of 29 students. This class action research was conducted as much as one cycle consisting of three meetings. The results of pretest data were given moments before the implementation of virtual laboratory media. Based on PhET (Physics Education Technology) simulation, the researcher got different results with the posttest given after the implementation of learning using virtual laboratory media by using PhET. The results of the pretest reached 25% on understanding of student concepts, and there was increased after using the media through posttest which is 75%. There was increased on percentage through understanding of student concepts in inclined plane materials using virtual laboratory media by 50%, the percentage of student learning motivation increased on inclined plane material by 28%, and in the data after using virtual laboratory media got a good category at 76%.